2015
DOI: 10.1016/j.visres.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Population representation of visual information in areas V1 and V2 of amblyopic macaques

Abstract: Amblyopia is a developmental disorder resulting in poor vision in one eye. The mechanism by which input to the affected eye is prevented from reaching the level of awareness remains poorly understood. We recorded simultaneously from large populations of neurons in the supragranular layers of areas V1 and V2 in 6 macaques that were made amblyopic by rearing with artificial strabismus or anisometropia, and 1 normally reared control. In agreement with previous reports, we found that cortical neuronal signals driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 48 publications
(85 reference statements)
1
68
0
Order By: Relevance
“…Several recent studies have looked at the performance of various decoders based on multiple simultaneously recorded, well-isolated single neurons or multi-unit sites (nonisolated neural signals) in V1 of anesthetized or awake, fixating macaques (Graf et al 2011, Berens et al 2012, Shooner et al 2015, Arandia-Romero et al 2016). Two common findings emerge from these studies.…”
Section: Decoding Neural Responsesmentioning
confidence: 99%
“…Several recent studies have looked at the performance of various decoders based on multiple simultaneously recorded, well-isolated single neurons or multi-unit sites (nonisolated neural signals) in V1 of anesthetized or awake, fixating macaques (Graf et al 2011, Berens et al 2012, Shooner et al 2015, Arandia-Romero et al 2016). Two common findings emerge from these studies.…”
Section: Decoding Neural Responsesmentioning
confidence: 99%
“…Interestingly, quantitative analyses show that the extent of neural abnormalities in V1 cannot explain the full range of visual deficits in amblyopia (Bi et al, 2011; Kiorpes, Kiper, O'Keefe, Cavanaugh, & Movshon, 1998; Kiorpes & McKee, 1999; Kiorpes & Movshon, 2004; Shooner et al, 2015). This may be due, at least in part, to a reduced strength of amblyopic eye input to higher level areas (Anderson, Holliday, & Harding, 1999; Anderson & Swettenham, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due, at least in part, to a reduced strength of amblyopic eye input to higher level areas (Anderson, Holliday, & Harding, 1999; Anderson & Swettenham, 2006). Thus, whereas V1 anomalies may be at the root of amblyopic impairments, they are likely to be amplified by the progressive degradation of feed-forward neural signals in the dorsal and ventral pathways (Barnes, Hess, Dumoulin, Achtman, & Pike, 2001; Choi et al, 2001; Conner, Odom, Schwartz, & Mendola, 2007; El-Shamayleh, Kiorpes, Kohn, & Movshon, 2010; Goodyear, Nicolle, Humphrey, & Menon, 2000; Ho & Giaschi, 2009; Imamura et al, 1997; Kiorpes, 2006; Kiorpes et al, 1998; Kiorpes & Movshon, 1996; Levi, 2006; X. Li, Dumoulin, Mansouri, & Hess, 2007; Muckli et al, 2006; Secen, Culham, Ho, & Giaschi, 2011; Shooner et al, 2015; Sincich, Jocson, & Horton, 2012). Indeed, several studies have shown reduced levels of activation for amblyopes than neurotypical observers as far downstream as parietal and ventral temporal cortex (Ho & Giaschi, 2009; Hyvarinen, Hyvarinen, & Linnankoski, 1981; Lerner et al, 2006; Secen et al, 2011; review by Anderson & Swettenham, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Using multi-electrode recordings from V1 and V2 in macaques with experimentally induced amblyopia, Shooner et al (2015) demonstrated that more information from the amblyopic eye is available at an early stage of cortical processing than would be expected based on behavioral contrast sensitivity losses. This implies deficits in downstream processing.…”
Section: Introduction To the Vision Research Special Issue On Amblyopiamentioning
confidence: 99%
“…This implies deficits in downstream processing. Shooner et al (2015) identified a reduction in the relative proportion of signals passing to extrastriate areas due to sub-optimal pooling of neural information from the …”
Section: Introduction To the Vision Research Special Issue On Amblyopiamentioning
confidence: 99%